2016
DOI: 10.1016/j.tsf.2015.11.082
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle layer deposition for highly controlled multilayer formation based on high-coverage monolayers of nanoparticles

Abstract: This paper establishes a strategy for chemical deposition of functionalized nanoparticles onto solid substrates in a layer-by-layer process based on self-limiting surface chemical reactions leading to complete monolayer formation within the multilayer system without any additional intermediate layers – nanoparticle layer deposition (NPLD). This approach is fundamentally different from previously established traditional layer-by-layer deposition techniques and is conceptually more similar to well-known atomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…Following addition of the nanoparticles, this peak diminishes drastically, indicating that the azide group participates in a chemical reaction. The alkyne C≡C stretch is also expected to appear in this spectral region; however, its intensity is normally very low and in previous studies it was not detected by IR for similar systems [17,29]. In addition, previous studies [17] showed that following the formation of the triazole ring, any unreacted azide can be titrated resulting in the complete disappearance of any absorption features in this spectral region, despite the presence of alkyne groups.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Following addition of the nanoparticles, this peak diminishes drastically, indicating that the azide group participates in a chemical reaction. The alkyne C≡C stretch is also expected to appear in this spectral region; however, its intensity is normally very low and in previous studies it was not detected by IR for similar systems [17,29]. In addition, previous studies [17] showed that following the formation of the triazole ring, any unreacted azide can be titrated resulting in the complete disappearance of any absorption features in this spectral region, despite the presence of alkyne groups.…”
Section: Resultsmentioning
confidence: 88%
“…Spectrum (a) in the N 1 s region shows two distinct features that can be deconvoluted into three components at 404.4 eV, 400.9 eV, and 399.4 eV. These components can be readily assigned to the nitrogen atoms of the azide group: N= N =N-, N =N=N- and N=N= N -, respectively (bolded and italicized for clarity) [17,38,40,41]. Density functional theory (DFT) calculations were performed to predict the binding energies of nitrogen atoms in the azide group and are represented by the colored lines beneath the experimental spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations